Magnesium promoted autocatalytic dehydrogenation of amine borane complexes: A reliable, non-cryogenic, scalable access to boronic acids. Issue 2 (11th January 2019) - Marciasini, Ludovic D.; Richard, Jimmy; Cacciuttolo, Bastien; Sartori, Guillaume; Birepinte, Melodie; Chabaud, Laurent; Pinet, Sandra; Pucheault, Mathieu
Abstract: Owing to the unusual reactivity of dialkylamine-borane complexes, a methodology was developed to simply access boronic acids. The intrinsic instability of magnesium aminoborohydride was tweaked into a tandem dehydrogenation borylation sequence. Proceeding via an autocatalytic cycle, amineborane dehydrogenation was induced by a variety of Grignard reagents. Overall, addition of the organomagnesium species onto specially designed dialkylamine-borane complexes led to a variety of boronic acids in high yields. In addition, the reaction can be performed under Barbier conditions, on a large scale. Graphical abstract: